Bioethanol production from cassava by fermentation process using Saccharomyces Cerevisiae - Rajandran, Kanagaraj (2013)
Bioethanol can be produced by fermentation of cassava,which carried out in conical flask by using Saccharomyces Cerevisiae.Objective of this experiment is to find out the effect of agitation speed,temperature and substrate concentrations on the bioethanol production,cell growth and the glucose consumption.At the end of this experiment,the best substrate concentrations of cassava,which leads to highest production of bioethanol and the highest cell growth can be identified.In this study substrate concentration varied as 25g(6.25%w/v),50g (12.5% w/v),75g(18.75% w/v), 100g(25% w/v) and 150g(32.5%w/v).Follows that,the effect of various fermentation temperature will be analyze, by using temperature varies as 20oC,30OC,40OC and 50oC.From this temperature vary the growth of yeast and the bioethanol production will be analyzed.Follows that,third parameter of this experiment is agitation speed of fermentation shake flask.Agitation speed varies from 0 rpm,150rpm,200 rpm and 250 rpm.For this part,effect of agitation speed on bioethanol production and cell growth of yeast studied.As for the optimum condition, temperature 30oC maintained, agitation speed fixed at 200 rpm,pH maintained at 4.5 and substrate concentration fixed about 100g(25% w/v).This experiment begins with inoculum preparation step,medium preparation step,following by transferring the inoculum into medium into 1L conical flask,fermentation of cassava in incubator shaker and lastly end with sample analysis.From the experiment,agitation speed 200 rpm,substrate concentration of 150g and temperature 40OC gives highest bioethanol production,highest cell growth and highest glucose consumption.